Inorganic Arsenite [As (III)] Represses Human Renal Progenitor Cell Characteristics and Induces Neoplastic-like Transformation - Md Ehsanul Haque; Swojani Shrestha; Donald A. Sens; Scott H. Garrett (Cells, 2025)
Arsenic, in the form of inorganic arsenite, is toxic to the kidney and can cause acute kidney injury, manifesting as destruction of proximal tubule cells. Nephron repair is possible through the proliferation of resident tubular progenitor cells expressing CD133 and CD24 surface markers. We simulated regenerative repair in the continued presence of i-As (III) using a cell culture model of a renal progenitor cell line expressing CD133 (PROM1) and CD24. Continued exposure and subculturing of progenitor cells to i-As (III) led to a reduction in the expression of PROM1 and CD24, as well as a decrease in the ability to differentiate into tubule-like structures. Cessation of i-As (III) and recovery for up to three passages resulted in continued repression of PROM1 and reduced ability to differentiate. Chronically exposed cells exhibited an ability to form colonies in soft agar, suggesting neoplastic transformation. Chronically exposed cells also exhibited an induction of CD44, a cell surface marker commonly found in renal cell carcinoma, as well as in tubular repair in chronic renal injury such as chronic kidney disease. These results demonstrate potential adverse outcomes of renal progenitor cells chronically exposed to a nephrotoxicant, as well as in environmental exposure to arsenic.